The development and validation of the hospital organizational environment scale for medical staff in China - Wang, Yu; Zhang, Jingwen; Feng, Xingmiao; Liang, Yan; Guan, Zhongjun; Meng, Kai (Frontiers in Public Health, 2023)
Objectives There is currently no measure of the hospital organizational environment targeting both clinicians and nurses in China. This study was conducted with the aim of developing and testing an instrument to assess the properties of the hospital organizational environment that is applicable to Chinese medical staff. Methods Items were developed based on a literature review, semi-structured interviews and an expert review and finalized based on corrected item-total correlation, content validity, construct validity, convergent validity, discriminant validity and reliability. The two samples for testing the first and final version of the Hospital Organizational Environment Scale (HOES) included 447 and 424 participants, respectively. Results The primary test, which comprised 18 items, contained four factors: hospital culture, work situation, organizational support and scientific research situation. The Cronbach’s alphas were 0.935, 0.824, 0.943, and 0.920, respectively. The results of the validation test showed that the questionnaire had good validity and reliability. Conclusion The HOES is a comprehensive instrument with demonstrated validity and reliability that can be adopted among medical staff to assess the organizational environment in hospitals.